1990
DOI: 10.1093/treephys/6.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three cold hardiness tests for conifer seedlings

Abstract: Greenhouse-cultured, container-grown ponderosa pine (Pinus ponderosa var. scopulorum Engelm.), interior Douglas-fir (Pseudotsuga menziesii var. glauca (Beissn.) Franco), and Engelmann spruce (Picea engelmannii (Parry) Engelm.) were cold acclimated and deacclimated in growth chambers over 19 weeks. Cold hardiness was measured weekly by a whole-plant freeze test and by two quick tissue tests: freeze-induced electrolyte leakage of needles, and differential thermal analysis of buds. The whole-plant freeze test pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 28 publications
1
81
0
1
Order By: Relevance
“…In the present study, values of that magnitude were obtained in April, after a distinct increase in the minimum air temperature. These results represent an additional corroboration of the method and indicate its suitability for quantifying the state of frost hardiness in plant tissues (Alexander et al, 1984 ;Burr et al, 1990).…”
Section: supporting
confidence: 69%
See 1 more Smart Citation
“…In the present study, values of that magnitude were obtained in April, after a distinct increase in the minimum air temperature. These results represent an additional corroboration of the method and indicate its suitability for quantifying the state of frost hardiness in plant tissues (Alexander et al, 1984 ;Burr et al, 1990).…”
Section: supporting
confidence: 69%
“…To assess the frost hardiness of plants, Flint et al (1967) suggested calculating an index of injury from the relative electric conductivities of solutions in which the samples had been incubated. This method has been widely adopted to test the frost hardiness of various parts of trees such as stem sections (van den Driessche, 1976), twigs (Alexander et al, 1984) and needles (Burr et al, 1990). More recently, Murray et al (1989) developed a method based on the rate of electrolyte leakage, which has been used successfully to quantify the freezing injury to woody shoots in, for example, Calluna vulgaris (Caporn et al, 1994), Quercus petraea (Deans et al, 1995) and Picea abies (Sheppard et al, 1995).…”
mentioning
confidence: 99%
“…Compared to the whole plant freeze test, FIEL of needle samples yields a more precise, quick, sensitive, and objective predictor of changes or differences in tissue cold hardiness (Burr et al, 1990). Because one-year-old red pine seedlings have a small quantity of needles, needles were randomly selected along the entire length of the shoot, carefully detached from seedlings, and rinsed with distilled water.…”
Section: Cold Hardinessmentioning
confidence: 99%
“…Samples were autoclaved (121 • C for 30 min) to achieve total cell death. Final conductivity readings were recorded after a second overnight leakage period (EC 2 ; following Burr et al, 1990). Blank vials were also measured and subtracted from EC 1 and EC 2 of each vial (Ritchie and Landis, 2003).…”
Section: Freeze-induced Electrolyte Leakagementioning
confidence: 99%